A utilização dos jogos como recurso didático no processo ensino - aprendizagem da matemática nas séries iniciais no estado do Amazonas - Bezerra, Célia Sandra Carvalho de Albuquerque (2009)
This research had for general objective to elaborate a set of games using the natural resources of the fauna and the flora of Amazon, to contribute in the improvement of the education process - learning of the Mathematics in the initial progression 6º and 7º year in the State of Education of Manaus. To reach this objective a bibliographical study was carried through that contemplated epistemological and pedagogical aspects related to education - Learning. The accomplishment of the State of the Art allowed in such a way to identify to different boarding’s on the use of the games in Education of the Mathematics in the Post graduation Courses Sense as in the Qualis Magazines. From this analysis and of the Methodology of the used Research a didactic resource called was elaborated Mathematical “Learning in Amazon” that consists of a Kit with 03 games approaching the contents of Rational numbers in its fractionary representations and Operations with positive and negative whole numbers. This research allowed going beyond the considered objective, a time that this resource can be used in other Sciences as Geography, History; Biology and Physics.